Java 11 cookbook : a definitive guide to learning the key concepts of modern application development. - Samoylov, Nick (Packt Publishing, 2017)
For more than three decades, Java has been on the forefront of developing robust software that has helped versatile businesses meet their requirements. Being one of the most widely used programming languages in history, it's imperative for Java developers to discover effective ways of using it in order to take full advantage of the power of the latest Java features. Java 11 Cookbook offers a range of software development solutions with simple and straightforward Java 11 code examples to help you build a modern software system. Starting with the installation of Java, each recipe addresses various problem by explaining the solution and offering insights into how it works. You'll explore the new features added to Java 11 that will make your application modular, secure, and fast. The book contains recipes on functional programming, GUI programming, concurrent programming, and database programming in Java. You'll also be taken through the new features introduced in JDK 18.3 and 18.9. By the end of this book, you'll be equipped with the skills required to write robust, scalable, and optimal Java code effectively.